Toward a Postcolonial Sociology: The View from Latin America - Bortoluci, José H; Jansen, Robert S (2013)
While sharing fundamental similarities with other colonial and post-colonial experiences, Latin America has a unique history of having been the proving ground for early Spanish and Portuguese imperial projects, of having experienced a relatively long duration of – but also historically early end to – these projects, and of negotiating a particular and complex trajectory of internal and external post-colonial relations. What can the study of this distinct colonial and post-colonial experience contribute to a broader program of postcolonial sociology? Conversely, what can a revitalized postcolonial sociology contribute to the study of Latin America? This article develops provisional answers to these questions by reviewing major currents in South and North American scholarship on the Latin American colonial and post-colonial experience. Some of this scholarship self-consciously identifies with broader movements in postcolonial studies; but much of it – both historical and contemporary – does not. By bringing together diverse strands of thought, this article sheds new light on what postcolonialism means in the Latin American context, while using the comparative leverage that this set of often overlooked cases provides to contribute to a new program of postcolonial sociology.
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé